Pengembangan Software Fisika Berbasis Android sebagai Media Belajar pada Materi Asas Black - Ismatullah, Kholida; Fathoni, Ahmad (Universitas Hamzanwadi, 2018)
This study aims to determine the influence in the Development of Android-Based Physics Software as a Learning Media in Black Basic Material Against the Achievement of Learning for Middle School Students in Selong District. The research method was used R & D by Sugiyono (2010). The research results used were 4 schools in Selong, there were SMPN 4 Selong, SMPN 1 Selong, SMP Lab. Hamzanwadi, and SMP Rekat Lauq, with a total sample of 175 people. Data collection techniques using questionnaires with Likert scale and data analysis techniques using feasibility tests. The results of this study indicate that android-based physics learning media are feasible to use with a percentage of 81.11%. Data analysis techniques to measure percentages using the calculation of the class average obtained from the pre test before being treated with the average post test after being given treatment, from the results seen an increase in student achievement in the four schools used as research samples. It is seen that the use of android-based learning media in physics lessons has an effect on improving students' physics learning achievements in Selong Junior Hight School.